Cold Radiofrequency Plasma Treatment Modifies Wettability and Germination Speed of Plant Seeds - Bormashenko, Edward (Nature Publishing Group, 2012)
We report the possibility to modify the wetting properties of the surfaces of a diversity of seeds including: lentils (Lens culinaris), beans (Phaseolus vulgaris) and wheat (Triticum, species C9) by cold radiofrequency air plasma treatment. Air plasma treatment leads to the dramatic decrease in the apparent contact angle. Moreover, the speed of germination and yield (germination rate) of seeds can be modified by preliminary plasma treatment. The change in the wetting properties of seeds is at least partially due to oxidation of their surface under plasma treatment. Significant growth of the peaks corresponding to the nitrogen containing groups in the mass spectra of air plasma treated seeds was registered by TOF-SIMS spectroscopy.